EGG PRODUCTIVITY AND EGG QUALITY IN EGG-LAYING CHICKENS FED WITH "PROBIOCORM" (Лучшие интеллектуальные исследования, 2025)
Abstract . This in the article “ ProBioKorm ” probiotic feed of the suffix egg-maker in chickens egg number efficiency and egg quality indicators impact studied . 45 days experience during egg number , weight , shell thickness and structural quality such as parameters control and experience groups in the section by comparison analysis The research was conducted probiotics without antibiotics in poultry farming stable productivity in provision important importance based on gives .